SAT0413 Infectious profile in a tuberculosis-endemic population with spondyloarthropathies. (15th June 2017) - Alzate, MA; Ramirez, F; Vargas, F; Hernandez-Parra, D; Salazar-Uribe, JC; Ortiz-Salazar, P; Pineda, R; ,
Abstract : Background: Screening latent tuberculosis (TB) and other opportunistic infections in patients with spondyloarthropathies (SpA) with biologic or immunosuppression therapy is important in highly endemic population (1). Objectives: To assess the prevalence of latent and active TB, hepatitis B, hepatitis C, HIV and Syphilis in a colombian cohort with SpA, as well as evaluate differences between treatments. Methods: A cross-sectional study was conducted in 621 patients with SpAs, in whom TB, hepatitis B, hepatitis C, HIV and syphilis screening was analyzed based on type of diagnosis. Differences among immunomodulatory therapies were assessed. Statistical association was examined by means of Chi-square tests, Mann-Whitney test, and logistic regression analyses. Results: The prevalence of latent and active TB in this cohort were 63, 1%, and 2, 9%, respectively. Significant differences were found in proportions of latent and active TB among types of SpAs, indicating a positive association with AS. A high proportion of TST conversion during immunotherapy was found. According to the immunomodulatory therapy, no differences were found among latent TB patients, active TB disease and no infection with the use of conventional DMARD therapy, but a positive association between latent TB and the use of biologic therapy was recognized. Low prevalences of opportunistic infections (i.e., Hepatitis B and C, syphilis and HIV) were found in this cohort, dispite the frequent use of biologic therapy. Conclusions: In a TB-endemic population, higher prevalences of latent and active TB were found in patients with SpAs, when compared to the general population. Complete infectious screening is mandatory in patients under consideration of biologic agents, and close follow-up must be done to recognize TST conversion. References: Pérez-Díaz CE, Uribe-Pardo E, Calixto OJ, Faccini-Martínez ΆA, Rodriguez-Morales AJ. Infections with biological therapy: strategies for risk minimization in tropical and developing countries. J Infect Dev Ctries. 2016;10(12). Disclosure of Interest: None declared